Distinct reduction in relative microglial glucose uptake compared to astrocytes and neurons upon isolation from the brain environment - Kunte, Sebastian T.; Gnörich, Johannes; Beumers, Philipp; Bartos, Laura M.; Wagner, Stephan; Wind-Mark, Karin; Holzgreve, Adrien; Pötter, Dennis; Werner, Rudolf A.; Ziegler, Sibylle; Albert, Nathalie L.; Colombo, Alessio; et al. (Frontiers in Cellular Neuroscience, 2025)
IntroductionMicroglial energy metabolism has gained attention for the treatment of neurodegenerative diseases. In vitro methods provide important insights; however, it remains unclear whether the metabolism of highly motile microglia is preserved outside their regular environment. Therefore, we directly compared the microglial glucose uptake in vivo and in vitro in mice.MethodsMicroglia and astrocytes were isolated from the brain using immunomagnetic cell sorting following [18F]FDG injection in living mice, followed by gamma and single-cell radiotracing (scRadiotracing). Enriched cell fractions were incubated with excess [18F]FDG (50,000-fold) in vivo, washed, and measured equivalently. For all fractions, radioactivity per cell was normalized to the injected or incubated radioactivity, and ratios of microglialuptake were calculated relative to astrocytes and the microglia/astrocyte-negative fraction. The experiment was repeated using a glucose-free buffer and validated by in vitro incubation without prior in vivo [18F]FDG injection to exclude the influence of fasting and glucose injection.ResultsscRadiotracing results were compared against cell culture [18F]-FDG incubation. The in vivo glucose uptake of microglia was higher when compared to astrocytes (50.4-fold, p < 0.0001) and non-microglia/ non-astrocyte cells (10.6-fold, p < 0.0001). Microglia still exhibited the highest glucose uptake in vitro, but with a distinct reduction in microglia-to-astrocyte (5.7-fold, p < 0.0015) and microglia-to-microglia/astrocyte-negative ratios (1.7 fold, p < 0.0001). Fasting and in vitro incubation were used to validate the results. Cell culture indicated low microglial uptake compared to that in neurons (1:100) or astrocytes (1:10).DiscussionCompared to astrocytes and other cells, microglia show a distinct reduction in uptake in vitro compared to in vivo uptake. Our results emphasize that in vitro experiments should be interpreted with caution when studying microglial energy metabolism.